Perceived discrimination and its association with self-rated health, chronic pain, mental health, and utilization of health services among Syrian refugees in Norway: a cross-sectional study - Dadras, Omid; Diaz, Esperanza (Frontiers in Public Health, 2024)
Background There is a scarcity of research on discriminatory experiences and their association with health outcomes among Syrian Refugees in Norway. Thus, this study aims to examine the relationship between perceived discrimination, self-rated health (SRH), chronic pain, poor mental health, and healthcare utilization among Syrian refugees resettled in Norway. Methods Cross-sectional data from the Integration for Health project were analyzed, including 154 Syrian refugees who resettled in Norway in 2018–19. Perceived discrimination, SRH, chronic pain, psychological distress, post-traumatic stress symptoms, and healthcare visits were assessed. Statistical analyses, including Poisson regression and multinomial logistic regression, were conducted. The significant statistical level was set at 0.05. Results Approximately 30% of participants reported experiencing discrimination, with no significant associations between sociodemographic factors and perceived discrimination. Perceived discrimination was significantly associated with psychological distress (adjusted PR: 2.07, 95%CI: 1.21–3.55), post-traumatic stress symptoms (adjusted PR: 11.54, 95%CI: 1.25–106.16), and 4 or more psychologist visits (adjusted OR: 12.60, 95%CI: 1.72–92.16). However, no significant associations were found between perceived discrimination and SRH; pain symptoms, or general healthcare utilization. Conclusion Experienced discrimination is highly prevalent and seems to be associated with mental health outcomes, but not clearly with SRH, pain, or general healthcare visits among Syrian refugees living in Norway. Efforts should focus on reducing discrimination, promoting social inclusion, and improving access to mental health services for refugees. Public awareness campaigns, anti-discrimination policies, and cultural training for healthcare professionals are recommended to address these issues and improve the well-being of Syrian refugees in Norway.